ANALISIS KINERJA INSTALASI FARMASI RSUD NOONGAN KABUPATEN MINAHASA DENGAN PENDEKATAN BALANCED SCORECARD (BSC) - Julianti Simei Sumolang; Widya Astuty Lolo; Gerald E. Rundengan (PHARMACON, 2021)
ABSTRACTThe increase of hospital quality and performance needs to be done to give a qualified service to societ. One method that can be used to find the Balanced Scorecard method is a coherent and comprehensive method as a management evaluation tool. This study aims to determine the performance of the Pharmacy Installation of Noongan District Hospital with the Balanced Scorecard (BSC) method from a financial perspective and an internal business process perspective. This research is descriptive with retrospective data collection for the financial perspective and prospectively for the internal business perspective. Primary date was obtained from direct observation and secondary data was obtained from financial administration reports of pharmacy installation and Noongan District Hospital. The results showed that from a financial perspective in 2020 an ITOR 3.25 times, average age of inventory 112 days, and the contribution of IFRS to RSUD 85.87%. From a internal business perspective, average dispensing time for non-concoction prescriptions is 16.10 minutes, drug availability rate is 90.71%, and concoction prescriptions in Pharmacy Installation which are usually given to children, are replaced with drugs that are already available according to the patient's illness, components Drug information given to patients still does not meet the standards set by the Minister of Health of the Republic of Indonesia No. 73 of 2016. Based on the results obtained, it can be concluded that the performance of the Pharmacy Installation of the Noongan Hospital is quite good, although improvements are still needed in terms of controlling drug supplies, dispensing time and drug information services. Keywords: Performance, Pharmacy Installation Noongan District Hospital, Balanced Scorecard ABSTRAKPeningkatan mutu dan kinerja rumah sakit perlu dilakukan untuk memberikan pelayanan yang berkualitas kepada masyarakat. Salah satu metode yang dapat digunakan ialah metode Balanced Scorecard yang merupakan metode yang koheren dan kompherensif sebagai alat evaluasi manajemen. Penelitian ini betujuan untuk mengetahui kinerja Instalasi Farmasi RSUD Noongan Kabupaten Minahasa dengan metode Balanced Scorecard (BSC) pada perspektif keuangan serta perspektif proses bisnis internal. Penelitian ini bersifat deskriptif dengan pengambilan data secara retrospektif untuk perspektif keuangan dan prospektif untuk perspektif bisnis internal. Data primer diperoleh dari observasi langsung dan data sekunder diperoleh dari laporan administrasi keuangan IFRS dan RSUD Noongan. Hasil penelitian menunjukkan bahwa pada perspektif keuangan tahun 2020 diperoleh ITOR 3,25 kali, average age of inventory 112 hari, dan kontribusi IFRS ke RSUD 85,87%. Pada perspektif bisnis internal diperoleh average dispensing time untuk resep non-racikan 16,10 menit, tingkat ketersediaan obat 90,71%, dan resep racikan di IFRS yang biasanya diberikan pada anak, diganti dengan obat yang sudah tersedia sesuai dengan penyakit yang diderita pasien, komponen informasi obat yang diberikan kepada pasien masih belum memenuhi standar yang telah ditetapkan oleh Permenkes RI No.73 Tahun 2016. Berdasarkan hasil yang diperoleh dapat disimpukan bahwa kinerja Instalasi Farmasi RSUD Noongan sudah cukup baik, walaupun masih perlu upaya perbaikan dalam hal pengendalian persediaan obat, dispensing time dan pelayanan informasi obat. Kata kunci: Kinerja, Instalasi Farmasi RSUD Noongan, Balanced Scorecard